Boring crustaceans shape the land–sea interface in brackish Caribbean mangroves. Issue 8 (10th August 2016) - Davidson, Timothy M.; Ruiz, Gregory M.; Torchin, Mark E.
Abstract: Consumer effects on the structure and extent of habitat‐forming foundation species such as trees and coral reefs are well known, but the role of non‐consumer interactions is less studied. Red mangroves are major foundation species at the land–sea interface, creating critical habitat in the tropics and subtropics. The complex aerial roots of mangroves ( Rhizophora mangle ) provide structural support to the tree and support diverse marine biota including boring isopods ( Sphaeroma terebrans ). These isopods frequently bore into root tips of mangroves causing atrophy, which can alter the structure and extent of mangrove habitat. We conducted a large‐scale isopod exclusion experiment across 18° of latitude at eight locations from Panama to Florida to test how isopods affect mangrove root structure and anchorage across a broad geographic range. We hypothesized that excluding isopods would increase root growth rates, morphological complexity, and anchorage compared to roots exposed to isopods. After one year, mangrove roots protected from boring isopods with cages increased growth by 2.5–19 times and exhibited a more complex morphology compared to uncaged controls. Further, 15% of caged roots became anchored in the sediment compared to none of the uncaged isopod‐inhabited roots. This suggests that these isopods, which are native to the Indo‐Pacific, are a major, widespread structuring agent of mangrove root habitat in the Caribbean and Florida, potentially limiting mangrove encroachment into estuarine waters.